ANALISIS PERAN KEPALA SEKOLAH DALAM PEMBERDAYAAN GURU - Wardana, Nyoman (Widyadari : Jurnal Pendidikan, 2019)
The prolonged economic, political and belief crisis that hit the Indonesian nation has had an impact on almost all aspects and order of life. Although it has caused a lot of deterioration to the nation and the people, one of the positive lessons that emerged was the emergence of basic thinking that fosters reform in various aspects of national life and statehood. The main focus of this reform is to create a civil society in the life of government, society and countries that have values ??of "Good Governance" that guide the values ??of democracy and an attitude of openness, honesty. justice, oriented to the interests of the people and accountable to the people (Koswara. 2000).          The government's desire to implement reforms in the life of nation and state in the field of education is more apparent with the issuance of Law Number 20 of 2003 concerning the National Education System (Sisdiknas). The substance of the new National Education System Law is evident from its vision: the realization of the education system as a strong and authoritative social institution to empower all citizens of Indonesia to develop into quality human beings who are able to proactively respond to the challenges of the times. One effort to improve the quality of existing education is to empower school principals. This is because the principal is the driving force for school resources, especially teachers and school employees. The role of the principal is so large in the process of achieving educational goals, so that it can be said that the success or failure of school activities is largely determined by the quality of the principal. All assets are utilized in such a way. Teachers need to be moved towards a positive, exciting and productive work atmosphere. However the teacher is an input whose influence is very large in the learning process. Likewise, physical and administrative arrangements or management need to be fostered so that discipline and enthusiasm for learning are high for students. This all requires the need for the implementation of educational leadership by a school principal.